Employment Law for Business - Bennett-Alexander, Dawn D. (Irwin, McGraw-Hill, 2017)
Two years ago. the first edition of this lext. the firs to be writen for business students, was pub- lished. While the authors and publisher belived that the issues were imporuinl. There was litlle ỉn the way of experience. since most colleges dicỉ not have an Employmcnt Law course. Our belieỉ was ihat il Ihe toxt was vvTÌtten, the course wou!d comc. To thai end. the publisher committed 10al- loNving Ihe lext to slart OLit slowly. and hopctuliy huiỉd a constitiiency in the years lo come. Rather ihan give up on the text and not take it to a second edition ií' there vvere only a few sales of the tìrst, the piibỉisher commitied lo ihe text for the long hau!.